Examining the Socio-economic Viewpoint of Nepalese Women Residing in Tokyo, Japan: A Study on Women's Migration to Japan - Saud, Padam (Journal of Durgalaxmi, 2023)
This study aims to determine the push factors and the pull factors driving Nepalese women to choose to work in Japan. It commonly occurs because of the push factor of fewer opportunities in the socio-economic situation and also because of pull factors in more developed areas. This study's general objective is to determine the socio-economic structure of female migrants from Nepal. Similarly, it also attempts to analyze the reasons, role, impact, and process of female migration, and the dynamics of foreign migration. This study adopts the qualitative design; data collection was done by interviewing 150 women and two focus group discussions (FGD) each of 10 informants in each group of 18-45 years old. The finding shows most importantly two types of factors: push and pull factors drive female migration. The finding indicates that poverty, unemployment, unequal wages, less importance of their role in the household, discrimination, poor health care, oppression, and socio-cultural barriers are the main push factors of female migration. More opportunities, equality, good education and health, high wages, technology, family and networks, safety and freedom, and empowerment through knowledge and income are the pull factors of Nepalese females.